2021
DOI: 10.31688/abmu.2021.56.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of burnout among teachers during the COVID-19 pandemic

Abstract: Évaluation du surmenage professionnel chez les enseignants pendant la pandémie du COVID-19Introduction. La fermeture des écoles et la transition vers l'enseignement en ligne, en raison des restrictions imposées par la pandémie du COVID-19, ont conduit à des changements majeurs dans le milieu de travail, ainsi qu'à l'émergence de diverses manifestations négatives sur la santé des enseignants, comme l'épuisement professionnel. L'objectif de l'étude était d'évaluer l'épuisement professionnel des enseignants penda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…Finally, work-related burnout is considered as motivating factor that can lead to burnout, which is in line with the study by (Cheptea et al, 2021). The study found that working online increased perceived stress.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Finally, work-related burnout is considered as motivating factor that can lead to burnout, which is in line with the study by (Cheptea et al, 2021). The study found that working online increased perceived stress.…”
Section: Discussionsupporting
confidence: 86%
“…However, the study found differences in burnout in different components. Cheptea et al (2021) assessed burnout among teachers in the Republic of Moldova during the covid-19 pandemic. It was found that working online increased perceived stress amongst 375 participants.…”
Section: Past Studies Past Studies On Working Onlinementioning
confidence: 99%
“…Two of the most important design options that are in particular relevant for teachers are related to: (1) Role topologies of doing scrum team work in education; and (2) Anchoring agile scrum in a course within an overall education program. As (1) has already been described in Loke (2020) and further information can be found there, we will focus below on design option (2).…”
Section: Design Optionsmentioning
confidence: 99%
“…This is the most applied framework in the professional work field around us, e.g., in small to medium enterprises, but also in big companies such as KPN, Amazon, and bol.com, etc. In a nutshell, scrum requires a scrum master to foster an environment where: (1) A product owner orders the work for a complex problem into a product backlog; (2) The scrum team turns a selection of the work into an increment of value during a sprint;…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, teachers have had to familiarize themselves with remote teaching methods and have experienced increased work stress owing to anxiety about teaching results (Ozamiz-Etxebarria et al, 2021 ; Silva et al, 2021 ). The sudden change in working environment and teaching methods may have increased work hours and the incidence of burnout in teachers (Cheptea et al, 2021 ; Lizana & Vega-Fernadez, 2021 ). In addition, teachers must cope with mental health problems caused by the pandemic as well as taking care of students with mental health problems (Naff et al, 2020 ; Weisbrot & Ryst, 2020 ; Zhou & Yao, 2020 ).…”
Section: Introductionmentioning
confidence: 99%